Systematic revision of the ormiine genera Aulacephala Macquart and Phasioormia Townsend (Diptera, Tachinidae) - Nihei, Silvio S. (Zootaxa, 2015)
The tribe Ormiini comprises 64 species in six genera. In the present paper, the ormiine genera Aulacephala Macquart and Phasioormia Townsend are revised, with two valid species recognized in the former and three valid species recognized in the latter. All available nominal species in Aulacephala and Phasioormia were examined and are revised herein, so that previous synonymies could be confirmed. Furthermore, Phasioormia papuana sp. nov. is described from Papua New Guinea and Indonesia, and Therobia punctigera (Paramonov, 1955) is proposed as a new synonym of Aulacephala hervei Bequaert, 1922, syn. nov. Keys to species and illustrations of male and female terminalia are provided for both genera.